Analisis Faktor Faktor Yang Mempengaruhi Produksi Kapulaga Di Desa Wandasari Kecamatan Taraju Kabupaten Tasikmalaya - Yuni Rahmah Nur Aqli; Trisna Insan Noor; Agus Yuniawan Isyanto (Jurnal Ilmiah Mahasiswa Agroinfo Galuh, 2022)
The research was carried out to know : The factors that affect the production of cardamom. The research was conducted using a survey method in Wandasari Village, Bojonggambir District, Tasikmalaya Regency. The population of cardamom farmers is 411 people by taking a sampel of 81 people at an error rate of 10%. The factors that influence the production of cardamom farming are analyzed using multiple linear regression equations. The parameter estimation is carried out using SPSS 25. The results showed that simultaneously the factors of land area, number of seeds, compost fertilizer, urea fertilizer, NPK fertilizer and labor affect cardamom production. As for partially, the number of seeds has a positive and significant effect, the factors of urea fertilizer, NPK fertilizer and labor has a positive but not significant effect. Meanwhile, land area and compost fertilizer have a negative effect on cardamom production in Wandasari Village, Bojonggambir District, Tasikmalaya Regency. The R2 value is 34,7%.